Use of Artificial Intelligence in Machine Design - Koivunen, Eelis (My University, 2024)
Machine design is a key part of mechanical engineering that involves creating and improving machines to meet given parameters and goals. Traditionally, designing machines has mainly depended on the knowledge and skills of engineers, focusing on making machines that work well, last long, and that can be made cost-efficiently. However, the rise of artificial intelligence (AI) brings exciting new possibilities. The purpose of this thesis is to examine the different ways of utilizing artificial intelligence to enhance the machine design process. Methods discussed are Computer-Aided Design (CAD) with AI, predictive design, generative design, simulations and predictive analysis. Furthermore, the thesis discusses the impact of AI on the engineering profession, including changes in job roles, education, and collaboration dynamics. It addresses ethical considerations and challenges associated with the responsible use of AI in machine design, emphasizing the importance of accountability and data security.
Keywords: artificial intelligence, machine design, generative design, predictive design, machine learning, deep learning, design optimization